Application of CRISPR/Cas9 genome editing system for molecular breeding of orchids - Endang Semiarti; Sri Nopitasari; Yuli Setiawati; Muhammad Dylan Lawrie; Aziz Purwantoro; Jaka Widada; Yasushi Yoshioka; Shogo Matsumoto; Kana Ninomiya; Yuuki Asano (Indonesian Journal of Biotechnology, 2020)
Orchid is an important ornamental plant in Indonesia due to their natural beauty of flowers. In the tropical forest, orchids are being acquired for trading and commercial market. Thus, the effort is required to proliferate orchid in large quantities for conservation and improve the floral variation for plant breeding. The purpose of this study is to develop a firmed methodology of molecular breeding of orchids using CRISPR/Cas9 KO system. The plant material used was Phalaenopsis amabilis protocorms growth on NP medium+pepton (2 g/L). Protocorm were submerged in the culture of Agrobacterium tumefaciens that Ti‐plasmid had been filled with a T‐DNA construct of a pRGEB32 vector harboring sgRNA with PDS3 sequence. Detection for transformants was confirmed by PCR using HPT primers (545 bp), Cas9 primers (402 bp), PDS primers (280 bp) and trnL‐F (1200 bp) as an internal control. The results showed that 0.96% PDS transformants were obtained from PDS3T2 lines. Several transformant showed pale leaf color compared to non‐transformant plants. This study suggests that the target gene has successfully edited by CRISPR/Cas9 system and could be applied for that functional gene editing in orchids.